1991
DOI: 10.1159/000261410
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride and Mutans Streptococci in Plaque Grown on Glass Ionomer and Composite

Abstract: The aim of this study was to compare the levels of fluoride and mutans streptococci in plaque grown on glass ionomer (Ketac-Fil) and composite (Silar) restorations in vivo. From tunnels left under the brackets bonded either with glass ionomer or composite, 14-day-old plaque samples were collected 14, 28, and 42 days after bonding. For glass ionomer the mean counts of mutans streptococci in plaque were 0.5 × 103, 6.7 × 103, and 8.8 × 103 CFU at the first, second, and third colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 9 publications
7
58
0
6
Order By: Relevance
“…The metal-fluoride complexes are also responsible for fluoride inhibition of protontranslocating F-ATPases and are thought to mimic phosphate to form complexes with ADP at the reaction center of enzymes. Indeed, ATPase plays an important role in the maintenance of intracellular pH by pumping out protons and in the inhibition of the enzyme that disrupts the bacterial metabolism and aciduric capability of Streptococcus mutans 17,[36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…The metal-fluoride complexes are also responsible for fluoride inhibition of protontranslocating F-ATPases and are thought to mimic phosphate to form complexes with ADP at the reaction center of enzymes. Indeed, ATPase plays an important role in the maintenance of intracellular pH by pumping out protons and in the inhibition of the enzyme that disrupts the bacterial metabolism and aciduric capability of Streptococcus mutans 17,[36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…14 Berg et al and Forss et al have found that the plaque adjacent to fluoride-releasing glass ionomers demonstrate lower levels of Streptococcus mutans. 15,16 Yoshiara et al found that the long-term use of a fluoride mouth rinse might contribute to the reduction of mutans streptococci. 17 Comparison between fluoride and probiotic group were statistically insignificant both the groups yielding similar results.…”
Section: Discussionmentioning
confidence: 99%
“…9 Glass ionomer cement presents a broad anticariogenic effect and is of great value in preventing secondary caries, even under conditions of a high caries risk. 10 This property made glass ionomer cement as the choice of restorative material for atraumatic restorative technique. However, whether the caries-inhibitor influence is sufficient to completely arrest the caries process is still doubtful.…”
Section: 5005/jp-journals-10026-1104mentioning
confidence: 99%
“…10 Freshly-mixed glass ionomer cements are antimicrobial against S. mutans and the mechanism of action is probably because of both fluoride and pH. 23 One study showed that there was no antibacterial activity despite the presence of fluoride in the agar around the set materials.…”
Section: Jofrmentioning
confidence: 99%